Count to sleep : trains - Gamble, Adam; Jasper, Mark ([Sandwich, Massachusetts] : Good Night Books, 2022)
All aboard! This adorable board book will have little conductors jumping for joy as they count all of their favorite types of trains including freight trains, steam locomotives, passenger trains, high-speed trains, commuter trains, subways, monorails, holiday trains, and more. Choo, choo!
On board pages.
Keywords: Counting -- Juvenile literature